A Survey of English Students Vocabulary Learning Strategies (VLS) - Kurniawan, Iwan; Indrasari, Nunun; Pradana, Satria Adi (Universitas Islam Negeri Raden Intan Lampung, 2020)
The objectives of this research are to know the kinds of vocabulary learning strategies, the most and the least vocabulary learning strategies, and strategy use based on gender differences. The methodology employed was survey with a research instrument questionnaire and interview. Results show Vocabulary Learning Strategies are Metacognitive, cognitive, memorization/repetition, and activation. Respondents tended to apply activation strategy as the highest, and it is indicated with a mean score (3.12). On the other side, the least utilized strategy was the memories/repetition strategy, and it is shown with the lowest mean score (1.87). Female students had a tendency to apply activation strategy, and it is indicated with the highest mean score (3.04) and least used memories/repetition strategies, and it is shown by mean score (1.84). In addition, the highest strategy employed by male students was also an activation strategy with mean score (3.0), and the lowest strategy was memories/repetition with the lowest score (1.51).